Syntactic and Morphological Analysis of Portfolio Reports of Kindergarten Teachers in Surabaya, Indonesia - Imelda Gozali; Faika Khairani (Universitas Dian Nuswantoro, 2021)
Abstract. As part of a community service project aimed at providing a customized English course to International Kindergarten teachers in Surabaya, Indonesia, this study investigated the types of grammatical (syntactic and morphological) errors made by the kindergarten teachers in the portfolio reports they wrote, and why the errors were committed. The data were taken from 9 (nine) portfolio reports of those teachers, and interview transcripts to three of them. The writers analyzed the errors using the Linguistic Category Taxonomy based on Dulay et al (1982) and categorized the reasons behind those errors into either Interlingual or Intralingual Errors (Richard, 1974). The result showed that Syntax – Noun Phrase type of error made up the biggest total number of errors (42 %), followed by Syntax – Verb Phrase (31%) and lastly, morphological – third-person singular incorrect (12%). This study also found that the most frequent source of errors is Intralingual in nature (89%). Overall, the results showed that any training aimed at those kindergarten teachers in particular, and in teacher training colleges in general, should address those most frequently committed errors. This Error Analysis on kindergarten teachers’ portfolio reports is the first in this field and constitutes a valuable input for teacher training colleges of Early Childhood Education program.Keywords: error analysis, interlingual error, intralingual error, kindergarten teachers, linguistic category taxonomy, portfolio reports, Abstrak. Sebagai bagian dari kegiatan pengabdian pada masyarakat yang bertujuan untuk memberikan pelatihan Bahasa Inggris kepada guru-guru PAUD internasional di Surabaya, Indonesia, penelitian ini menyelidiki tipe-tipe kesalahan tata Bahasa (dari segi sintaks dan morfologi) yang dilakukan oleh guru-guru PAUD dalam menulis rapor portofolio anak didik, dan juga mengapa kesalahan tersebut terjadi. Data diambil dari 9 (Sembilan) rapor portofolio para guru PAUD tersebut, beserta transkrip wawancara kepada tiga guru. Penulis menganalisis kesalahan tersebut dengan menggunakan Taksonomi Kategori Linguistik berdasarkan Dulay et al (1982). Sumber kesalahan tersebut dibagi ke Interlingual atau Intralingual, menurut Richard (1974). Hasil penelitian ini menemukan bahwa total kesalahan terbesar (42%) terjadi pada bidang Sintaks yaitu pembentukan Noun Phrase, diikuti oleh bidang Sintaks juga yaitu pembentukan Verb Phrase (31%), dan yang terkahir adalah bidang Morfologi yaitu kesalahan bentuk orang ketiga tunggal (12%).Pada keseluruhan, hasil tersebut menunjukkan bahwa pelatihan Bahasa Inggris bagi para guru PAUD tersebut pada khususnya, maupun pada institusi keguruan pada umumnya, perlu memperhatikan aspek sintaks dan morfologi tersebut di atas. Error Analysis pada rapor portofolio ini baru pertama kali ini dilakukan, dan dapat memberi sumbangan berarti pada pengajaran Bahasa Inggris di institusi keguruan PAUD di Indonesia.Kata kunci: analisis kesalahan, Bahasa Inggris, guru PAUD, kesalahan interlingual, kesalahan intralingual, rapor portofolio, taksonomi kategori linguistik